2020
DOI: 10.1155/2020/9234083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fermentation Using Lactobacillus plantarum A6 on the Physicochemical and Functional Properties of Precooked Sorghum bicolor and Voandzeia subterranea Blended Flour

Abstract: The present study is aimed at producing Sorghum bicolor and Voandzeia subterranea complementary instant flour. The precooked sorghum and Bambara groundnut flours were mixed at different proportions (0 : 100, 25 : 75, 50 : 50, 75 : 25, and 100 : 0), hydrated with sterile distilled water (1 : 3, w:v), and fermented for 72 h/37°C using Lactobacillus plantarum A6 at 105 CFU/g. During the fermentation, samples were withdrawn for pH, titrable acidity, and microbial analyses. After fermentation, color, particle size,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…The result is consistent with the pattern observed by Ogodo et al . (2018) in their research on lactic acid bacteriafermented soybean flour and Ntsamo et al (2020) on fermentation on sorghum flour properties. Giami and Bekebain (1992) also found that longer fermentation durations greatly reduced the microbial activity of food products that have low water absorption capacities.…”
Section: Resultsmentioning
confidence: 99%
“…The result is consistent with the pattern observed by Ogodo et al . (2018) in their research on lactic acid bacteriafermented soybean flour and Ntsamo et al (2020) on fermentation on sorghum flour properties. Giami and Bekebain (1992) also found that longer fermentation durations greatly reduced the microbial activity of food products that have low water absorption capacities.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, antinutrient levels were reduced throughout fermentation (Jagati & Debasmita Dash, 2021;Rathore et al, 2016;Singh & Raghuvanshi, 2012). Ntsamo et al (2020) observed an ideal blend of fermented precooked Bambara groundnut (75%) and sorghum flour (25%) with Lactobacillus Plantarum A6 (105 CFU/g) for meal replacement in children's diets. Similarly, Lactobacillus acidophilus and Saccharomyces boulardii are used to ferment little millet to improve its biochemical quality.…”
Section: Fermentationmentioning
confidence: 99%
“…Ready-to-use flour is one of instant products that has been developed. Sorghum has been prepared to be instant flours and processed into several food products [4,5]. There are several technologies to prepare instant flour such as drum drying [6], spray drying , and extrusion [7].…”
Section: Introductionmentioning
confidence: 99%